Pastoral production systems and land utilisation types - Leeuw, P.N. de (International Livestock Research Institute, 1984)
Describes West African transhumant pastoralism, briefly analysing major characteristics of this mode of production, reviews differences in land tenure & farm size, livestock holdings, labour intensity, income & level of technical knowledge of African pastoral & cropping systems, and assesses applicability & efficacy of FAO's land evaluation framework in covering the distinctive features of these production systems.